2021
DOI: 10.1038/s41598-021-00515-z
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in adaptation of medial-lateral gait parameters during split-belt treadmill walking

Abstract: The split-belt treadmill has been used to examine the adaptation of spatial and temporal gait parameters. Historically, similar studies have focused on anterior-posterior (AP) spatiotemporal gait parameters because this paradigm is primarily a perturbation in the AP direction, but it is important to understand whether and how medial-lateral (ML) control adapts in this scenario. The ML control of balance must be actively controlled and adapted in different walking environments. Furthermore, it is well establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…This strategy may reflect a preference for a more stable, symmetric gait pattern in older people, particularly when touch sensitivity is impaired. Kinematic studies found older people show a reduced medio-lateral shift of the centre of mass (COM) – a strategy which is more robust towards perturbations and prioritizes maintaining mediolateral balance – compared to young adults who shift their body centre away from the fast foot during split-belt treadmill walking leading to an asymmetric balance control that may be metabolically more efficient (Afschrift et al, 2019; Fettrow et al, 2021). Indeed, older people who are destabilised through visual perturbations increase step width to gain stability (De Sanctis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy may reflect a preference for a more stable, symmetric gait pattern in older people, particularly when touch sensitivity is impaired. Kinematic studies found older people show a reduced medio-lateral shift of the centre of mass (COM) – a strategy which is more robust towards perturbations and prioritizes maintaining mediolateral balance – compared to young adults who shift their body centre away from the fast foot during split-belt treadmill walking leading to an asymmetric balance control that may be metabolically more efficient (Afschrift et al, 2019; Fettrow et al, 2021). Indeed, older people who are destabilised through visual perturbations increase step width to gain stability (De Sanctis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As the primary aim of our study was descriptive, the explanatory or causal interpretations of the possible neuronal origins of these three spatiotemporal patterns should be made with caution. Recording 3D kinematics would allow assessment of the link between neural activity and locomotor behaviour more directly, for example by manipulating mediolateral stability through experimental perturbations (De Sanctis et al, 2022; Fettrow et al, 2021). In addition, the limited number of EEG channels available did not allow us to perform a source reconstruction of the signals, which would have provided a clearer neurophysiological understanding of the current results and delineate the cortical regions involved in the neural control of gait.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies have found that older adults show poorer adaptability in comparison to younger adults in both manual adaptation paradigms with visual perturbation (e.g., Anguera et al, 2011;Bock, 2005;Fernandez-Ruiz et al, 2000;Seidler, 2006Seidler, , 2007Wolpe et al, 2020) and mechanical perturbation (e.g., Huang & Ahmed, 2014). In contrast, other studies using locomotor adaptation paradigms did not observe differences in adaptation rates between younger and older adults (e.g., Bakkum et al, 2021;Malone & Bastian, 2016;Vervoort et al, 2019; but see Fettrow et al, 2021). Taken together, prior findings hint at an inverted-u relationship between age and sensorimotor adaptability across the lifespan with performance peaking in young adulthood.…”
Section: Introductionmentioning
confidence: 95%
“…Since then, countless studies have explored compensatory processes using powerful tools and analyses (for recent reviews, see Bunzeck et al, 2024; Fettrow et al, 2021; Poirier et al, 2021). These studies have considerably advanced the description and understanding of age-related neural alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies reported a positive correlation (Cassady, Gagnon, et al, 2020; Clark et al, 2014; Harada et al, 2009; Heuninckx et al, 2008; Holtzer et al, 2015; Jor’dan et al, 2017; Larivière et al, 2019; Mattay et al, 2002; Spedden et al, 2019), and as many reported no correlation or even a negative correlation (Bernard & Seidler, 2012; Cassady et al, 2019; Cassady, Ruitenberg, et al, 2020; Fernandez et al, 2019; Hawkins et al, 2018; Holtzer et al, 2016; Loibl et al, 2011; Riecker et al, 2006; Ward et al, 2008). Several reasons may explain these discrepancies (for reviews see Fettrow et al, 2021; Morcom & Johnson, 2015; Poirier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%